2015
DOI: 10.1016/j.procs.2015.07.169
|View full text |Cite
|
Sign up to set email alerts
|

Context-Aware Computation Offloading for Mobile Cloud Computing: Requirements Analysis, Survey and Design Guideline

Abstract: Along with the rise of mobile handheld devices the resource demands of respective applications grow as well. However, mobile devices are still and will always be limited related to performance (e.g., computation, storage and battery life), context adaptation (e.g., intermittent connectivity, scalability and heterogeneity) and security aspects. A prominent solution to overcome these limitations is the so-called computation offloading, which is the focus of mobile cloud computing (MCC). However, current approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…However, as stated by [59], while coexistence and deployment are reaching high results, adaptation scenarios and ease of use require further investigation. For this reason the research can reasonably be focused on an effective distributed resource management strategy, hosted on the mobile device.…”
Section: Overall Results and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as stated by [59], while coexistence and deployment are reaching high results, adaptation scenarios and ease of use require further investigation. For this reason the research can reasonably be focused on an effective distributed resource management strategy, hosted on the mobile device.…”
Section: Overall Results and Limitationsmentioning
confidence: 99%
“…Regarding the development of Mobile Cloud Computingapplications, Orsini et al [59] identified six main requirements: availability, portability, portability, scalability, usability, maintainability and security. Among these, to reach the scalability requirement, one of the most used approach is to partition the application into tasks of different granularity level, although it involves some major difficulties such as:…”
Section: Computation Offloading For Mobile Systemsmentioning
confidence: 99%
“…In order to develop a comprehensive list of general requirements for MEC applications, we started bottom‐up with adapted ISO requirements and merged them from a top‐down perspective with specific requirements inferred from the application scenarios presented in the previous section to ensure the requirements have practical relevance. The resulting list is summarized in the following (further details can be found in the work of Orsini et al).…”
Section: Main Requirementsmentioning
confidence: 99%
“…Chen [7] have also suggested a decentralized computation offloading game in which resource constrained mobile devices wait and learn about the state of surrogates before offloading computational tasks depending on their resource availability. Also Orsini et al [21] have proposed a context-aware mechanism for computation offloading in which mobile devices decide when and how to offload based on their state and resource capacities. Moreover, Cuervo et al [6] presented a fine grained energy aware computation offloading mechanism dubbed MAUI.…”
Section: Related Workmentioning
confidence: 99%